SISTEM INFORMASI PENJUALAN KENDARAAN BERMOTOR BERBASIS WEB DI CV. SETIA PURI LEGENDA: sales information system, Web, UML - Hidayat, Fendi (LP2M Universitas Nurdin Hamzah, 2018)
CV. Setia Puri Legenda is a company engaged in the sale and purchase of used vehicles both motorcycles and cars. During this time the sales process is still using manual system. Therefore, to improve its business process in this research will be made a web based vehicle sales information system in CV. Setia Puri Legenda. In this study using waterfall system design method with UML modeling to describe the system to be built. The system is built using PHP programming language and MySql database